Analisis Keamanan Database dalam Menghadapi Ancaman Kebocoran Data di Perusahaan Teknologi Informasi - Nisa Alifatuzzahra (STIKes Ibnu Sina Ajibarang, 2025)
Information technology companies rely heavily on databases to store critical data that is vulnerable to leaks that can be financially and reputationally detrimental. This study aims to analyze the effectiveness of database security mechanisms, especially encryption and access control, in preventing data leaks. The method used is a case study with a qualitative approach through observation and interviews at information technology companies, as well as technical analysis of database protection implementation. The results of the study show that to maintain data security, companies need to use end-to-end encryption and a biometric login system so that only authorized people can access it. Smart technology such as AI is also important for detecting threats quickly. In addition, using special tools to monitor devices and routinely test security helps reduce risks. No less important, providing security training to employees so that they are more vigilant and do not become a gap for data leaks. In this way, companies can be better prepared to face various threats in today's digital era.